The legal‐normative conditions of police transparency: A configurational approach to open data adoption using qualitative comparative analysis. (10th April 2017) - Ingrams, Alex
Abstract : In the United States, there is mounting political pressure on public agencies to publish internal data. But transparency policy innovation brings a unique set of legal and normative challenges regarding how sensitive information will be used. It is therefore an open question as to what legal‐normative conditions favour innovation. Are there specific kinds of laws, rules, or normative conditions that are related to adoption of new, potentially risky, transparency policies? In this article, qualitative comparative analysis with secondary data from multiple sources is used to find out what configurations of conditions are associated with open data use in 122 police departments. Results show three different paths to innovation among police departments: mandate driven, city‐stakeholder convergence, and network learning. The findings are examined and developed through interviews with experts from a national police transparency initiative.